Digital Bank User Acceptance Analysis Using The Extended Technology Acceptance Model - Dicky Jhon Anderson Butarbutar; Asri Ady Bakri; Nurlaili Rahmi; Novrini Hasti; Aprih Santoso (Jurnal Sistim Informasi dan Teknologi, 2023)
The Covid-19 pandemic requires banks to provide electronic payments, carry out digital transformation and open up opportunities for financial technology-based companies. Digital transformation in banking requires reliable integration and security between systems. Otherwise, it can become a gap for cyber attacks. Cyber security in banking includes Confidentiality, Integrity, Availability, Non-repudiation, and Authentication. Jenius is the first digital bank in Indonesia that makes it easy for customers to complete transactions and manage finances digitally without going to the bank. This bank was once a victim of a cyber attack that attacked customers with material losses of around 50 billion and non-material losses in the form of decreased bank credibility. Digital Bank also has problems that often occur, such as failing to identify customers, differences in facts on proof of transfer, frequent force close applications, etc. This study aims to determine the effect of security on behavioral intention and other factors that influence behavioral choice in this digital bank using the modified Technology Acceptance Model (TAM) model. The variables used are Confidentiality, Integrity, Availability, Non-repudiation, Authentication, Perceived Security, Perceived usefulness (PU), Perceived Trust, Perceived Ease of Use (PEoU), and Behavioral Intentions. This research uses quantitative methodology by distributing questionnaires to 200 sample customers. The measurement results show that more than half variables are accepted. The four rejected variables are the Confidentiality, Availability, and Non-repudiation variables to perceived security and the Perceived Ease of Use (PEoU) variable for the trust variable. Future research can add several external variables and review the rejected variables.